Covid-19 and the Disruption of Islamic Religiosity in Contemporary Indonesia; From Traditional Rituals to Virtual Rituals - Abd Hannan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2021)
This study examines the phenomenon of disruption of religious religiosity among Muslim communities in Indonesia, as well as their acceptance of digital platform-based religious facilities during the Covid-19 pandemic. By using qualitative research methods and analysis of studies based on postmodern sociological theory, this study obtained three findings; 1) During the Covid-19 pandemic, social activities in Indonesia experienced quite strict restrictions and tightening of crowds, including socio-religious activities. In this regard, sacred religious activities that were previously carried out openly in places of public worship such as mosques, prayer rooms, churches, were all carried out separately and separately, turning to virtual worship through the use of digital applications such as Zoom, Google meet, and the like; 2) In general, the emergence of these new rites is accepted by the majority of Indonesian Muslims, and has even become a new religiosity phenomenon that is often found in many religious activities. Mainstream Muslim organizations in Indonesia, Nahdhatul Ulama and Mumahammadiyah, support the policy of sterilizing public places of worship. However, for the virtualization of religion, within certain limits, both of them criticize and even refuse to virtualize religion in totality, except for religious rituals that are only celebrations or slametans such as tahlilan and istigasah; 3) In the context of the dynamics of Islamic rites in Indonesia, the shift in religiosity among the Muslim community can be found in a number of socio-religious activities such as virtual tahlil, virtual tarawih, virtual haul, virtual gatherings on holidays, even religious activities that have a mandatory law to be held regularly. congregation is like the Friday prayer at the mosque.